Acceptability of escitalopram versus duloxetine in outpatients with depression who did not respond to initial second‐generation antidepressants: Study protocol for a randomized, parallel‐group, non‐inferiority trial. Issue 4 (18th September 2019) - Yokoi, Yuma; Nakagawa, Atsuo; Yoshimura, Naoki; Furukawa, Toshiaki A.; Mimura, Masaru; Iwanami, Akira; Abe, Takayuki; Nakagome, Kazuyuki
Abstract: Aim: The purpose of this study is to compare acceptability of two second generation antidepressants for major depressive disorder patients who have not responded to the first antidepressant for current episode. We will investigate the treatment discontinuation rate and treatment adherence as well as incidence of adverse events in order to evaluate safety. Methods: This is a two‐arm, three‐phased randomized controlled trial in which independent assessors will be blinded while treating psychiatrists and patients remain unblinded to treatment allocation. Patients will be randomized to escitalopram or duloxetine in Step 1 (8 weeks), and when entering Step 2 (8 weeks), the drug will be switched to the other if the first one is not effective at the end of Step 1. The acceptability of the allocated drugs, improvements in depression from baseline, adverse events, and attrition rates will be recorded and assessed for up to 52 weeks, including the follow‐up step. Results: It is going to be disseminated via our following reports or presentations. Conclusions: This study will provide valuable information for clinicians who encounter patients who failed to respond to their first treatment. Abstract : This is a protocol of randomized controlled trial assessing acceptability of two antidepressants after one antidepressant therapy failed.